Analysis of the impact of land use on floating object in rivers at different spatial scales—the Chongqing section of the Three Gorges Reservoir area - Ye, Sheng; Pei, Desheng; Zhang, Xiaocheng; Luo, Yachen; Liu, Jian; Chen, Lin (Frontiers in Ecology and Evolution, 2023)
Floating object pollution in the Three Gorges Reservoir area(TGRA) is a serious environmental problem. It directly harms the safety of the reservoirs. Currently, relevant research has only focused on certain aspects, such as the salvage and treatment of floating objects, and little has been done on the underlying causes of floating object. The way humans use land will have a large influence on floating object in rivers, but the relationship between the two still needs to be further explored. We used remote sensing images to obtain the distribution of floating objects in the Chongqing section of the TGRA, and combined that with current land use data to study the relationship between land use and river floating objects. We found that: ①The number of floating object spots in the main stream of the Yangtze River gradually increased from the upper reaches (the main urban section of Chongqing) to the lower reaches (northeast section of Chongqing), while the opposite was true in the tributaries of the Yangtze River. ②Under different buffer scales, urban, rural residential, farmland, gardenland, grassland and other land use types were positively correlated with the number of floating debris spots in the river, and the correlation order was rural residential > farm land > urban> gardenland > grassland > forest. ③When the buffer radius was 1.5 km, the land use comprehensive intensity index (LUI) had the highest interpretation degree to the number of floating debris spots, with a rate of 68.8%. To the best of our knowledge, this was the first attempt to study the relationship between land use types, the LUI and river flotsam, and it was also the first study of the relationship between river flotsam and land use in the upper reaches of the Yangtze River. Factors influencing floating object in the Chongqing section of the TGRA were further explored, which can provide a reference for floating object treatment work, as well as for territorial spatial planning and ecological protection.